Majeed Amjad's belief in Man, Universe and Allah - Dr. Zafar Huassain Haral; Dr. Zeab Un Nisa Harral; Ayesha Kanwal (Zaban-o-Adab, 2024)
Majeed Amjad was a prominent Urdu poet of modern era. He studied Arabic and Persian literature in his early age from his maternal grandfather, so the technique of poetry, Arooz, may be .After getting his early education from Jhang, he moved to Lahore for his graduation before independence .That was the time when Nazam was the popular with respect to Ghazal in subcontinent literary circles. So Majeed Amjad preferred Nazam to express his thoughts commonly. In this article I have concluded from the analysis of his poetry that he developed a strong bonding of love for Nature, Man and Allah. Majeed Amjad is a poet of modern Urdu Nazam who achieved a clear connection between Man, Universe and Allah not as the traditionalist believes. This article proves with the examples from his poetry that he believes in Allah and loves Nature and was not a pessimist.